A joint training of healthcare line managers and health and safety representatives in facilitating occupational health interventions: a feasibility study protocol for the Co-pilot project - Lundmark, Robert; Agrell, Alexander; Abildgaard, Johan Simonsen; Wahlström, Jens; Tafvelin, Susanne (Frontiers in Psychology, 2024)
Healthcare employees are experiencing poor wellbeing at an increasing rate. The healthcare workforce is exposed to challenging tasks and a high work pace, a situation that worsened during and after the COVID-19 pandemic. In turn, exposure to these high demands contributes to poor health, increased turnover, reduced job satisfaction, reduced efficacy, and reduced patient satisfaction and safety. Therefore, it is imperative that we identify measures to mitigate this crisis. One piece of this puzzle is how to implement sustainable tools and processes to improve the work environment of healthcare organizations. In this paper, we present the study protocol for the outlining and piloting of a joint training for pairs of healthcare line managers and their associated health and safety representatives in a Swedish healthcare organization. The objective of the training is to aid and advance the implementation of interventions to improve the work environment at the unit level. Following recommendations in the literature, the training is based on a stepwise approach that considers the specific context and focuses on the involvement of employees in creating interventions based on their needs. A central component of the training is the development of the pairs’ collaboration in prioritizing, developing, implementing, and evaluating the interventions. The training is based on an on-the-job train-the-trainer approach in which participants are progressively trained during four workshops in the steps of a participatory intervention process. Between these workshops, the pairs follow the same progressive steps together with their employees to develop and implement interventions at their unit. The pilot will involve four pairs (i.e., eight participants) representing different parts and functions of the organization and will be conducted over a period of three months. We will use a mixed method design to evaluate preconditions, the process, and proximal transfer and implementation outcome factors of the training. The overall aim of the pilot is to appraise its feasibility and be able to adjust the training before a potential scale-up.